2011
DOI: 10.1111/j.1468-1331.2011.03547.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke mechanism in patients with non‐valvular atrial fibrillation according to the CHADS2 and CHA2DS2‐VASc scores

Abstract: Increased frequency of concomitant PCSE and that of the atherothrombotic mechanism may explain the high risk of stroke in patients with higher CHADS(2) /CHA(2) DS(2) -VASc score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…Our data are in line with previous studies that found that the risk of cerebral atherosclerosis increases as CHA 2 DS 2 -VASc score increases [34]. Similarly, Kim et al [35] showed that a high CHADS2 score group more frequently had combined extracranial and intracranial stenosis and proximal stenotic lesions of the symptomatic artery.…”
Section: Discussionsupporting
confidence: 82%
“…Our data are in line with previous studies that found that the risk of cerebral atherosclerosis increases as CHA 2 DS 2 -VASc score increases [34]. Similarly, Kim et al [35] showed that a high CHADS2 score group more frequently had combined extracranial and intracranial stenosis and proximal stenotic lesions of the symptomatic artery.…”
Section: Discussionsupporting
confidence: 82%
“…We additionally hypothesized that the stroke etiology was entirely different in the treatment group. For instance, ischemic stroke may be caused by carotid atherothrombosis in the patients with NVAF under dabigatran therapy (16). However, ASCOD subtyping revealed that the potential involvement of etiologies other than cardioembolism was similar in both groups, and thus the stroke severity-reducing effect of dabigatran was not a result of the differences in stroke etiology.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple potential mechanisms of thrombosis have been proposed in AF patients which can be associated with, but not necessarily caused by, proximate arrhythmia occurrence. 37,38 In addition, it is clear that our current risk scoring systems also identify patients at risk for stroke independent of the presence of AF. 39 In one study of 860 patients with AF and a history of stroke, 39% had other potential cardiac sources of embolism beyond AF and 27% had a concomitant possible atherothrombotic mechanism of stroke.…”
Section: Is There a Way To Reconcile The Data For And Against An Assomentioning
confidence: 99%
“…The association of these alternative sources of stroke in patients with AF was significantly correlated with increasing CHADS 2 /CHA 2 S 2 -VASc scores. 38 Other 37 Additionally, patients can have nonthromboembolic strokes because of multiple factors, including hypertension or in situ thrombosis, which have no mechanistic relationship with AF. Therefore, it should not come as a surprise that patients with a history of AF can have thromboembolic events without proximate AF episodes.…”
Section: Is There a Way To Reconcile The Data For And Against An Assomentioning
confidence: 99%